2005
DOI: 10.1063/1.1906331
|View full text |Cite
|
Sign up to set email alerts
|

Direct observation of copper depletion and potential changes at copper indium gallium diselenide grain boundaries

Abstract: We have used micro-Auger electron spectroscopy, cathodoluminescence spectroscopy, and work function measurements in copper indium gallium diselenide polycrystalline solar cell films cleaved in ultrahigh vacuum. We establish that, relative to the grain interior, the grain boundary shows (1) a Cu composition decrease, as large as a factor of two, (2) a work function decrease of up to 480 meV, and (3) no additional radiative recombination centers despite a high concentration of grain boundary (GB) defects. These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
82
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(87 citation statements)
references
References 12 publications
(5 reference statements)
4
82
0
Order By: Relevance
“…In contrast, the VBM is not changed substantially at Se-Se-terminated GBs [9]. Surface-sensitive, experimental studies have shown Cu depletion and In enrichment at GBs in polycrystalline CuðIn; GaÞSe 2 thin films [10], whereas bulk-sensitive analyses have so far not reported any changed composition [11,12]. The disagreement of these results may be due to different GB properties on surfaces (Ref.…”
mentioning
confidence: 43%
“…In contrast, the VBM is not changed substantially at Se-Se-terminated GBs [9]. Surface-sensitive, experimental studies have shown Cu depletion and In enrichment at GBs in polycrystalline CuðIn; GaÞSe 2 thin films [10], whereas bulk-sensitive analyses have so far not reported any changed composition [11,12]. The disagreement of these results may be due to different GB properties on surfaces (Ref.…”
mentioning
confidence: 43%
“…[13][14][15] The effect of this internal offset at the GBs could be of similar importance as it is at the surface of the absorber, 33 whereas, there is ample experimental evidence for the Cu-poor surface layer 34,35 and its beneficial consequences for the performance of CIGS solar cells as long as the overall film composition is Cu-poor, 36 the question whether or not such a Cu-poor layer is a general positive feature of GBs in CIGS is still under discussion. [37][38][39][40] The present study concentrates on investigating the effect of such an internal band offset and on finding the conditions that have to be fulfilled if the Cu-poor layer should have a decisive beneficial effect on the performance of polycrystalline CIGS solar cells. Figure 10 shows the band diagram of a GB surrounded by a Cu-poor layer that has a valence band offset ⌬E V toward the CIGS bulk.…”
Section: A Excess Barrier Heightmentioning
confidence: 99%
“…It has been proposed that GBs in CIGS feature a hole barrier due to a Cu-poor layer surrounding the GB, 13,15 which would strongly reduce GB recombination. Here, we obtain an analytical expression that models the recombination rate at such a barrier by assuming different GB capture cross sections it,n and it,p for electrons and holes.…”
Section: Introductionmentioning
confidence: 99%
“…Typical examples are the carefully engineered Cu deficient GBs in CIGS solar cells 23,24 and a high temperature CdCl2 treatment for CdTe solar cells 24,25 .…”
mentioning
confidence: 99%